Caracterização da equideocultura no estado de Minas Gerais - E.R. Vieira; A.S.C. de Rezende; A.M.Q. Lana; K.M.C. Barcelos; J.M. Santiago; J. Lage; M. G. Fonseca; J.A.G. Bergmann (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2015)
Recently, horse breeding has achieved greater prominence in the Brazilian society and now it started to appear as a part of the Brazilian agribusiness. The state of Minas Gerais stands out as the main producer of equidae in Brazil. The aim of this work was to characterize the breeding of equidae in this State in order to support future researches in this sector. By the evaluation of records from 1990 to 2009 provided by the "Brazilian Institute of Geography and Statistics" (IBGE) and also 967 interviews with breeders of equidae, it was possible to characterize some important points. It was observed that equidae breeding in this State moves over R$1,500,000,000 per year and employs 86,000 people. The main investments of the properties are made in purchasing saddles, accessories and commercial feeds. The main goal of equidae breeders in Minas Gerais has been the work in rural properties (49.49%) complementing many farming activities, especially the work with cows. Although Minas Gerais holds the main herd of equidae in the country, the number of animals has decreased. On the one hand, the equidae breeding sector has demonstrated its social and economic importance in agribusiness; on the other, hand further researches are needed to develop public policies to improve the breeding of equidae in Minas Gerais.